2018
DOI: 10.1016/j.juro.2017.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Retroperitoneal Lymph Node Dissection for Clinical Stage I Nonseminomatous Germ Cell Tumors of the Testis: Safety and Efficacy Analyses at a High Volume Center

Abstract: In the context of a high volume center laparoscopic retroperitoneal lymph node dissection was safe and its oncologic efficacy was comparable to that of open surgery. Select patients with stage I nonseminomatous germ cell tumor could be offered laparoscopic retroperitoneal lymph node dissection as an alternative to other options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Retroperitoneal lymph node dissection (RPLND) is recommended for nonseminomatous germ cell tumors (NSGCTs) with a residual mass of over 1 cm after chemotherapy on radiographic imaging according to the European Association of Urology (EAU) guidelines. Previous studies of laparoscopic RPLND (L-RPLND) have shown feasibility but difficulty because of perinodal and perivessel fibrosis and adhesions [2, 3]. Robot-assisted L-RPLND (R-RPLND) has proven its advantages with regard to high-definition three-dimensional visualization, increased freedom of instrument movement, and minimization of tremors.…”
Section: Introductionmentioning
confidence: 99%
“…Retroperitoneal lymph node dissection (RPLND) is recommended for nonseminomatous germ cell tumors (NSGCTs) with a residual mass of over 1 cm after chemotherapy on radiographic imaging according to the European Association of Urology (EAU) guidelines. Previous studies of laparoscopic RPLND (L-RPLND) have shown feasibility but difficulty because of perinodal and perivessel fibrosis and adhesions [2, 3]. Robot-assisted L-RPLND (R-RPLND) has proven its advantages with regard to high-definition three-dimensional visualization, increased freedom of instrument movement, and minimization of tremors.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely, however, that side effects would differ from what is generally known from recent primary laparoscopic RPLND series (postoperative complication rate 0-9.8%) [31]. In a large series by Nicolai et al [32] only 8/221 patients (3.6%) who underwent laparoscopic RPLND had a complication with Clavien-Dindo grade >2. Nevertheless, patients with a suspicion of TGCT but without evidence of TGCT on testicular pathology (two patients in our series) were unnecessarily subjected to an invasive procedure.…”
Section: Discussionmentioning
confidence: 90%
“…In a large series by Nicolai et al. only 8/221 patients (3.6%) who underwent laparoscopic RPLND had a complication with Clavien–Dindo grade >2. Nevertheless, patients with a suspicion of TGCT but without evidence of TGCT on testicular pathology (two patients in our series) were unnecessarily subjected to an invasive procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Several factors have been evaluated to estimate the risk of recurrence and described in the past [ [17] , [18] , [19] ]. The proportion of embryonal carcinoma, the proliferation rate and the lymphovascular invasion [ 20 ] have been described as prognostic factors of recurrence [ 17 , 19 , 21 ]. In multivariate analysis, lymphovascular invasion [ 20 ] overruled the other risk factors and is therefore used to stratify stage I NSGCT into “high risk” and “low risk” groups.…”
Section: Risk Factors For Stage I Nsgctsmentioning
confidence: 99%
“…The proportion of embryonal carcinoma, the proliferation rate and the lymphovascular invasion [ 20 ] have been described as prognostic factors of recurrence [ 17 , 19 , 21 ]. In multivariate analysis, lymphovascular invasion [ 20 ] overruled the other risk factors and is therefore used to stratify stage I NSGCT into “high risk” and “low risk” groups. Patients without lymphovascular invasion (LVI–) on histopathological report of orchiectomy represent the pathological stage pT1 and the clinical stage IA.…”
Section: Risk Factors For Stage I Nsgctsmentioning
confidence: 99%